Trends in Retinopathy of Prematurity - Divya Jain; Vikrant Sharma; Ruchi Rai (Delhi Journal of Ophthalmology)
The World Health Organization has identified retinopathy of prematurity (ROP) as an emerging cause of childhood blindness in developing and middle-income countries. The screening criteria differ in developed and developing world. With increasing survival of preterm babies and setting up of more neonatal intensive care units in developing countries including India, an overhaul of the developments and current understanding of pathophysiology, risk factors, and management options are required. In countries such as India, there is a shortage of workforce and expertise required for ROP. Telemedicine for ROP has been implemented in many areas of the world to overcome this and artificial intelligence (AI)-based prediction is being explored worldwide. AI as an additional screening tool can improve efficacy for ROP screening and may lead to automated, quantifiable, and objective diagnosis in ROP.